2021
DOI: 10.1111/jonm.13282
|View full text |Cite
|
Sign up to set email alerts
|

Professional autonomy in nursing: An integrative review

Abstract: Aim To summarize knowledge of professional autonomy in nursing. Background Professional autonomy is associated with experienced meaningfulness of the work. This refers to participation in decision‐making and the ability to influence working practices. Evaluation In an integrative review, relevant studies were retrieved from four databases. Quality was systematically evaluated using critical appraisal tools. PRISMA guidelines were followed. Inductive content analysis was used to analyse current knowledge of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 46 publications
(127 reference statements)
9
113
0
3
Order By: Relevance
“…In our findings, professional autonomy may significantly predict job satisfaction among nurses acting as PAs, consistent with comprehensive literature reviews in a range of contexts, such as with nurses in different care settings [ 52 , 53 ] and PAs worldwide [ 44 , 54 ]. It can be supported by self-determination theory (SDT), which identifies three basic psychological needs—autonomy, competency, and relatedness—as determinants of satisfaction [ 55 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our findings, professional autonomy may significantly predict job satisfaction among nurses acting as PAs, consistent with comprehensive literature reviews in a range of contexts, such as with nurses in different care settings [ 52 , 53 ] and PAs worldwide [ 44 , 54 ]. It can be supported by self-determination theory (SDT), which identifies three basic psychological needs—autonomy, competency, and relatedness—as determinants of satisfaction [ 55 ].…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, the outcomes of professional autonomy motivate nurses to apply their knowledge and skills and foster professionalism; thus, in literature reviews [ 53 , 59 ], it has been found to enhance job satisfaction, commitment, retention of nurses, and clinical outcomes for patients. Conversely, Mastekaasa [ 60 ] reported no relationship between autonomy and job satisfaction among physicians, nurses, teachers, and social workers in Norway.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are highly educated professionals with professional autonomy and accountability to secure the safety and health of their patients (Porter-O'Grady, 2019;Pursio et al, 2020). Without effective distributional decision-making structures throughout the organisation, nurses are left in the role of employees with no ownership of their work and no accountability, forcing them to forget their professional role (Hess, 2011;Porter-O'Grady, 2019).…”
Section: Magnet Principles As a Guiding Forcementioning
confidence: 99%
“…Without effective distributional decision-making structures throughout the organisation, nurses are left in the role of employees with no ownership of their work and no accountability, forcing them to forget their professional role (Hess, 2011;Porter-O'Grady, 2019). There are certain legal restrictions relating to nurses' professional autonomy (Pursio et al, 2020), and shared decision-making is particularly challenging when applied to issues generally controlled by management such as resources, recruitment of personnel and budgets (Scherb et al, 2011).…”
Section: Magnet Principles As a Guiding Forcementioning
confidence: 99%
“…Organizational efforts to strengthen nurses' autonomous motivation, through supportive supervisor and coworker behaviors, should prove to be a beneficial strategy for contributing to a well-rooted workforce in the profession. Among the possible means to facilitate such efforts, healthcare managers, including supervisors in departments or units, could promote a culture of support, for example by encouraging equity in the application of policies and relying on shared leadership (Pursio et al, 2021). The finding that supportive coworker behaviors would be particularly important to facilitate nurses' autonomous motivation adds to the relevance of bringing particular attention to shared leadership in which team members with particular knowledge, skills or abilities assume greater leadership in some areas of their work.…”
Section: Implications For Nursing Managementmentioning
confidence: 99%